Resilience in children and multidimensional thinking as a social transforming factor - Alvarán-López, Sandra Milena; Carrero-Torres, Cindy Tatiana; Castellanos-Triviño, Héctor Rafael; Pinilla-López, Heidy Yohanna (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The child and adolescent populations have been some of the primary victims of the armed conflict in Colombia. Physical, cognitive, and psycho-affective damages are the major consequences of childhood exposure to a long history of violence in the country. Against this background, it is important to demonstrate that when a boy, a girl, or an adolescent participates in communities of inquiry as educational psychology scenarios with a social perspective, they become more resilient and they strengthen their internal protection mechanism for dealing with risk factors or marginalization caused by the conflict. This article presents the results of the research Promotion of resilience among children victims of the armed conflict, contributions from communities of inquiry, which was based on the empirical-analytical paradigm. This quasi-experimental study follows a quantitative approach. It involved children and adolescents from families that were victims of the Colombian armed conflict, inhabitants of the municipalities of Villavicencio, in Meta, and Soacha, in Cundinamarca.